Delays in the decision to seek care and associated factors among mothers who delivered in rural health centers in Wolaita Zone, Southern Ethiopia - Gelaw, Kelemu Abebe; Atalay, Yibeltal Assefa; Zerefu, Firehiwot; Gebeyehu, Natnael Atnafu (Frontiers in Global Women's Health, 2024)
Background: delay in the decision to seek care in health facilities during pregnancy and childbirth can potentially lead to adverse outcomes for women with obstetric complications. These complications lead to maternal mortality and morbidity in developing countries such as Ethiopia. The magnitude and underlying causes of maternal first delay in Ethiopia, particularly in rural areas of the country, are not well documented. This study aimed to assess the magnitude of delay in the decision to seek care and associated factors among mothers who gave birth in rural health centers in Wolaita Zone, Southern Ethiopia. Method and materials: A facility-based cross-sectional study was done among mothers who gave birth in rural health centers of Wolaita Zone, Southern Ethiopia from June 30, 2020- to July 30, 2022. A sample size of 410 study participants was selected from each public health center using the systematic random sampling method. Data were collected from a pre-tested and structured questionnaire using an Open Data Kit; analysis was carried out using SPSS version 25. Identification of the determining factors for the first delay was done using binary logistic regression. Variables with a P value of less than 0.25 in binary analysis were selected for multivariable analysis. The variables with a P value less than 0.05 were considered statistically significant. Results: The magnitude of delay in the decision to seek care in health facilities was 42.1% among mothers who gave birth in rural health centers in the Wolaita Zone, Southern Ethiopia. Unemployed mothers[AOR, 2,529; 95% CI, 1.546, 4.136], husbands with no formal education[AOR, 1.290; 95% CI, 1.029, 1.616], mothers who had negative attitudes towards seeking care in health facilities, and [AOR; 1.695; 95% CI, 1.061, 2.709] were significantly associated with a delay in the decision to seek care at a health facility. Conclusion: The magnitude of the first maternal in the decision to seek care at health facilities among mothers was high in the study area. Efforts should be to strengthen husbands’ literacy levels and household income through various income-generating approaches. Additionally, disseminating health information can effectively raise community awareness of the importance of institutional delivery.